The Influence of Individual Characteristics, Work Placement and Work Environment on Employee Performance at CV. Enam Jaya - *Ine Luna Dianti; Nelly Rosaline (Universitas Syiah Kuala, 2022)
The purpose of this study is to see how individual characteristics, work placement, and work environment affect employee performance. CV. Enam Jaya has employees with characteristics who are less careful in recording stock inventories, so they often experience cases where the stock reports do not match the warehouse stock, lack of work among employees, which results in many pending tasks, lack of planning in carrying out tasks. In terms of an inadequate work environment such as lack of air cleanliness in the room, hot air temperature and disturbing noise. CV. Enam Jaya has a population of 50 employees using the quota sampling technique which is used in research that has a limited number of samples. The data processing method in this study used Minitab version 20. The research data used were primary data obtained through distributing questionnaires. The analytical tool used is multiple linear regression test. The results of the study indicate that: There is a positive and significant effect of the Work Environment on Employee Performance, but there is no influence of Individual Characteristics and Work Placement on Employee Performance.